Aging, Spirituality, and Narrative: Loss and Repair - Baldwin, Clive; Carty, Brian; Estey, Jennifer (Narrative Works)

(untitled) (The University of New Brunswick, 2015)
In this paper, we explore how narrative loss may impact upon one’s sense of self and the spiritual process of meaning-making and purpose. We argue that we are narrative beings that make sense of our selves and our social, physical, and ideational worlds in and through narrative and that this process, which involves matters of purpose, truth, and values, is at one and the same time a spiritual activity, as both spirituality and narrative involve a sense of openness and indeterminacy, and the generation of meaning and purpose. As we age, however, physical, mental and social changes may disrupt how we narrativize our lives, and social and ideological (or meta-) narratives might frame what stories we can tell, and how we can tell them, in ways different from the past. We explore some of the narrative losses associated with aging and then, drawing on practices in spiritual direction, discuss some possible ways of countering such losses, in particular the development of narrative literacy, the re-ignition of narrative desire, the making of narrative connections, and the deepening of autobiographical reasoning. In this way, we hope to illustrate how narrative works in the spiritual lives of older adults.